Pathogenic insights from Huntington's disease-like 2 and other Huntington's disease genocopies. Issue 6 (December 2016) - Margolis, Russell L.; Rudnicki, Dobrila D.
Abstract : Purpose of review: Huntington's disease-like 2 (HDL2) is a rare, progressive, autosomal dominant neurodegenerative disorder that genetically, clinically, and pathologically closely resembles Huntington's disease. We review HDL2 pathogenic mechanisms and examine the implications of these mechanisms for Huntington's disease and related diseases. Recent findings: HDL2 is caused by a CTG/CAG repeat expansion in junctophilin-3 . Available data from cell and animal models and human brain suggest that HDL2 is a complex disease in which transcripts and proteins expressed bidirectionally from the junctophilin-3 locus contribute to pathogenesis through both gain-and loss-of-function mechanisms. Recent advances indicate that the pathogenesis of Huntington's disease is equally complex, despite the emphasis on toxic gain-of-function properties of the mutant huntingtin protein. Summary: Studies examining in parallel the genetic, clinical, neuropathological, and mechanistic similarities between Huntington's disease and HDL2 have begun to identify points of convergence between the pathogenic pathways of the two diseases. Comparisons to other diseases that are phenotypically or genetically related to Huntington's disease and HDL2 will likely reveal additional common pathways. The ultimate goal is to identify shared therapeutic targets and eventually develop therapies that may, at least in part, be effective across multiple similar rare diseases, an essential approach given the scarcity of resources for basic and translational research.